Spirituality in palliative care in Brazil: an integrative literature review - Esperandio, Mary; Leget, Carlo (REVER: Revista de Estudos da Religião, 2020)
Considered to be one of the essential dimensions of Palliative Care (PC), spirituality has undergone rigorous scientific research in the United States and Europe. In Brazil, the implementation of PC services and the discussion on the integration of spirituality in this context are relatively recent. This study presents the current state of the art on this subject. Searches were carried out in the CAPES Journals Portal, Virtual Health Library, SciELO and PUBMED. Twenty-five studies were selected for analysis, and 17 had a central focus on spirituality in PC. The literature evidences a growing understanding about the role of spirituality in this context; the need for theoretically founded research and of practical models of spiritual care; lack of professional training in relation to the subject and lack of knowledge about the importance of specialized spiritual assistance. For the advancement of knowledge in this field, future studies should consider these gaps and potentialities.